Curcuphenol possesses an unusual histone deacetylase enhancing activity that counters immune escape in metastatic tumours - Ellis, Samantha L. S.; Dada, Sarah; Nohara, Lilian L.; Saranchova, Iryna; Munro, Lonna; Pfeifer, Cheryl G.; Eyford, Brett A.; Morova, Tunc; Williams, David E.; Cheng, Ping; Lack, Nathan A.; Andersen, Raymond J.; et al. (Frontiers in Pharmacology, 2023)
Curcuphenol, a common component of the culinary spices, naturally found in marine invertebrates and plants, has been identified as a novel candidate for reversing immune escape by restoring expression of the antigen presentation machinery (APM) in invasive cancers, thereby resurrecting the immune recognition of metastatic tumours. Two synthetic curcuphenol analogues, were prepared by informed design that demonstrated consistent induction of APM expression in metastatic prostate and lung carcinoma cells. Both analogues were subsequently found to possess a previously undescribed histone deacetylase (HDAC)-enhancing activity. Remarkably, the H3K27ac ChIPseq analysis of curcuphenol-treated cells reveals that the induced epigenomic marks closely resemble the changes in genome-wide pattern observed with interferon-γ, a cytokine instrumental for orchestrating innate and adaptive immunity. These observations link dietary components to modifying epigenetic programs that modulate gene expression guiding poised immunity.